'It's Powerful' The impact of involving children and young people in developing paediatric research agendas: A qualitative interview study - Laura Postma; Malou L. Luchtenberg; A. A. Eduard Verhagen; Els L. M. Maeckelberghe (Wiley, 2024)
Abstract Introduction There is a growing consensus that children and young people (CYP) should be involved in matters that concern them. Progress is made in involving CYP in developing pediatric research agendas (PRAs), although the impact of their involvement remains unknown. We aimed to evaluate the impact of involving CYP in developing PRAs and assess the extent to which postpatient and public involvement (post‐PPI) activities were planned. Methods We conducted a qualitative study using in‐depth interviews to identify and gain an in‐depth understanding of the impact of involving CYP in developing PRAs. The transcripts were uploaded to Atlas.ti to be coded and organised. Dutch‐language interviews were analysed and interpreted together with vocational education and training (VET) students. These students were aged between 14 and 18 years and were training to become nurses. Results Three CYP and 15 researchers decided to participate. We focused on three categories of impact: agenda‐setting impact, individual impact and academic impact. Involving CYP creates a more enriched and clarified agenda. It ensured that both CYP and researchers underwent personal or professional growth and development, it created a connection between the people involved, awareness about the importance of involving CYP and it ensured that the people involved had a positive experience. The participants were unable to indicate the academic impact of their PRAs, but they did understand the key factors for creating it. In addition, the need to measure impact was highlighted, with a particular focus on assessing individual impact. Discussion Our study outlines the diverse subthemes of impact that arise from involving CYP in developing PRAs. Despite the potential of research agendas to amplify CYP voices, only a minority of researchers strategized post‐PPI activities ensuring impactful outcomes, prompting the need for thorough evaluation of various impact forms and consistent alignment with the overarching goal of transforming the research field. Patient or Public Contribution We involved VET students in the data analysis and interpretation phase by forming a young person advisory group. The data analysis of the interviews analysed by the VET students revealed four distinct themes: 1. Learnt new knowledge. 2. Learnt to collaborate. 3. Learnt to listen. 4. Assessment of the individual impact.